Comparative Evaluation of the Efficacy of Irrigation Delivery Systems on Enterococcus faecalis - Bhat, Raksha; Shetty, Preethesh; Hegde, Mithra N. (Journal of Dentistry Indonesia, 2018)
Attaining a sterile root canal system is important since microorganisms can cause persistent inflammation in the periradicular tissues. Objectives: This study sought to evaluate the efficacy of two irrigation delivery systems; the EndoVac and semiconductor diode laser irradiation with 5.25% sodium hypochlorite and 2% chlorhexidine. Methods: Fifty teeth were disinfected according to the Occupational Safety and Health Administration regulations. The teeth were then instrumented, followed by inoculation with bacterial strains of Enterococcus faecalis (ATCC 29212). The teeth were randomly assigned to five groups, Group I: Control group; Group II: Teeth irrigated with 5.25% NaOCl + Endovac; Group III: Teeth irrigated with 2% Chlorhexidine + Endovac; Group IV: Teeth irrigated with 5.25% NaOCl + laser irradiation; and Group V: Teeth irrigated with 2% Chlorhexidine laser irradiation. All samples were incubated on Muller–Hilton media plates for a period of 24 h. We determined the colony-forming units and analyzed them statistically using Fisher’s exact test. Results: Laser irradiation completely disinfected the root canal system. The EndoVac system produced significant disinfection but was comparatively less effective than laser irradiation. Conclusion: Laser irradiation had a significantly greater bactericidal effect than the EndoVac system, used in conjunction with sodium hypochlorite and chlorhexidine.